International Finance Theory and Policy - Suranovic, Steve (Open textbook library., 2010)
International Finance Theory and Policy is built on Steve Suranovic's belief that to understand the international economy, students need to learn how economic models are applied to real world problems. It is true what they say, that ”economists do it with models.“ That's because economic models provide insights about the world that are simply not obtainable solely by discussion of the issues. International Finance Theory and Policy develops a unified model of the international macroeconomy. The text provides detailed descriptions of major macroeconomic variables, covers the interest rate parity and purchasing power parity theories of exchange rate determination, takes an exhaustive look at the pros and cons of trade imbalances and presents the well-known AA-DD model to explore the effects of fiscal and monetary policy under both fixed and flexible exchange rates. The models are developed, not by employing advanced mathematics, but rather by walking students through a detailed description of how a model's assumptions influence its conclusions. But more importantly, each model and theory is connected to real world policy issues. The Finance Text has the following unique features: o Begins with an historical overview of the international macroeconomy to provide context for the theory. o Concludes with a detailed discussion of the pros and cons of fixed and floating exchange rate systems. o Provides an extensive look at the issue of trade imbalances. Readers learn techniques to evaluate whether a country's trade deficit (or surplus) is dangerous, beneficial, or benign. o Explains how purchasing power parity is used to make cross country income comparisons. o Offers clear detailed explanations of the AA-DD model. o Applies the AA-DD model to understand the effects of monetary and fiscal policy on GDP, the exchange rate, and the trade balance. International Finance Theory and Policy by Steve Suranovic is intended for a one-semester course in International Finance. After March 2010, you can check out the entire book online or request a desk copy.